The Determinants of the Net Asset Value of Sharia Mutual Funds in Indonesia - Miftahul Huda; Mufti Afif; Meichio Lesmana; Zuhria Febriana Putri (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Purpose - Determine an influence on the determinants of NAV (Net Asset Value) of Islamic mutual funds for the 2017-2021 period in IndonesiaDesign/methodology/approach -. The study uses a quantitative methodology. The data used are secondary data as time series. The data analytics technique uses the Vector Auto Regression (VAR) model and the Vector Error Correction (VECM) model. Data treatment using Eviews 10 and Microsoft Excel 2019.Findings - The results show that the variables significantly affect the net asset value of Islamic mutual funds. All variables have a negative effect, except BI7DRR that has a positive short-term effect. Simultaneously, all variables had no significant effect on the net asset value of Islamic mutual funds. The NAV reacted positively to the shocks of inflation, money supply, BI7DRR and ISSI, whereas the exchange rate reacted negatively. The most significant contribution to the net asset value of sharia mutual funds is itself. While the lowest contribution is the monetary supply and the ISSI.Research Limitations/Implications - The qualitative methods used have limitations that can be enhanced by combining other methods. for the data obtained, macroeconomic data and net asset value of Sharia Mutual Funds in Indonesia. Therefore, the results may only be applicable in Indonesia.Practical implications - Practitioners are advised to tend to look at the condition of BI7DRR which is determined by its policy through Bank Indonesia (BI) as a reference for consideration in making decisions to invest.Social implications - This research is expected to provide benefits to academics as a review of the sciences related to this research and can develop it.Originality/Value – To our knowledge, the period considered by the researcher is the last five periods, from 2017 to 2021. The search method used is VAR/ VECM which is used to measure and analyze the short-term and long-term influence of the variables.